Fine mapping of Plasmodium falciparum ribosomal phosphoprotein PfP0 revealed sequences with highly specific binding activity to human red blood cells (2010)
The Plasmodium falciparum P0 ribosomal phosphoprotein (PfP0) was identified for the first time by screening a cDNA expression library of P. falciparum parasites with sera from malaria-immune individuals. Due to its localization on the surface of different parasite life-cycle stages (merozoites and gametocytes) and its recognition by invasion-blocking antibodies, PfP0 has been considered a potential malaria-vaccine component. In this study, 16 20-mer-long synthetic peptides spanning the entire PfP0 sequence were evaluated by means of receptor-ligand assays with human red blood cells (RBCs) in order to determine the role played by these peptides in the invasion process. Four RBC high-activity binding peptides (HABPs), located mostly toward the N-terminal region, were identified: HABP 33898 (1MAKLSKQQKKQMYIEKLSSL 20), HABP 33900 (41ASVRKSLRGKATILMGKNTRY60), HABP 33901 (61IRTALKKNLQAVPQIEKLLPY 80), and HABP 33906 (161LIKQGEKVTASSATLLRKFNY180). The binding pattern of HABPs 33898 and 33906 to enzyme-treated RBCs suggests receptors of protein nature for these two HABPs, one of which could correspond to a common 58-kDa RBC membrane protein, as indicated by results of cross-linking assays. Both HABPs exhibited high content of ?-helical features and prevented P. falciparum merozoite invasion to RBCs in vitro by up to 91%. The invasion-blocking ability reported here for these PfP0 HABPs supports their inclusion in immunological studies with the aim of assessing their potential as candidates for a vaccine against P. falciparum malaria. © 2009 Springer-Verlag.